Experimental Investigation of Compressive Strength and Infiltration Rate of Pervious Concrete by Fully Reduction of Sand - Aneel Manan; Mushtaq Ahmad; Fawad Ahmad; Abdul Basit; Muhammad Nasir Ayaz Khan (Civil Engineering Journal, 2018)
The aim of the study is to investigate compressive strength of pervious concrete by reduction of fine aggregate from zero to 100%, additionally investigate infiltration rate of pervious concrete. Experimental study has conducted at Cecos Engineering University Peshawar. The pervious concrete samples were produced for 7 and 28 days. Compressive strength of pervious concrete indicated higher reduction of the sand reduces compressive strength and almost 50% compressive strength decreased by reduction of 100% sand from the design mix. On the other side, infiltration rate for 28 days shows direct relation above 40% reduction of sand and highest 273% of infiltration rate by reducing 100% sand from the design mix. The 90% reduction of sand from concrete give considerable compressive strength of 2150 psi and infiltration rate of 165.79 inch/hour, which can be recommended for pavements of parking and walking area.